Włoskie inicjacje Aleksandra Wata - Pietrych, Krystyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article presents the stages of Aleksander Wat’s first journey to Italy in 1949 – starting from Venice, through Florence and Rome, finishing in Naples and Capri. Most of all, the article interprets the poetic records of the places visited by the poet and his impressions written down in letters. As a result, what the journey to Italy becomes for Wat is not only a discovery of the beauty of landscape and the plenty of art, but, most importantly, an experience of physical contact with the Mediterranean land, an initiation into the fascinating witnessing of the incarnation of cultural tradition into a visible landscape, a sensual initiation into the legacy of the Mediterranean. The coda of the text is his unexpected reminiscence from the first journey to Italy recorded in a social realist drama.